Role of Serum B-type Natriuretic Peptide before and after 2hours of Spontaneous Breathing Trial among Patients under Mechanical Ventilation - Hoque, AKM Faizul; Mazumder, Manas Kanti; Any, Omma Hafsa; Moin, Sharna; Gupta, Rocky Das; Polash, Shahadat Hossain; Mondol, Rajan; Alam, Sheikh Ul (Journal of Current and Advance Medical Research, 2021)
Background: Weaning of a patient from mechanical ventilation is very important for the outcomes of the patients. Objective: The purpose of the study was to evaluate the serum level of BNP before and after 2hours of spontaneous breathing trial (SBT) among patients under mechanical ventilation. Methodology: This prospective cohort study was conducted in the Department of Anesthesia, Analgesia and Intensive Care Medicine at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh over a period of 2 years. Study population was selected for weaning from mechanical ventilation support for the first time in the age group of more than 18 years with both sexes. Plasma BNP level of all patients was measured before and after 2 hours of spontaneous breathing trial. Results: A total number of 30 patients were recruited for this study. One-third (33.3%) of the patients failed on SBT. The mean percent changes of BNP (pg/ml) during 2-h of SBT in weaning success and failure groups were 38.41±9.379 and 59.51±2.940 respectively (p=0.01). The receiver-operating characteristic curve analysis for BNP as a predictor of weaning outcome, showed that the area under the curve (AUC) was 0.89. Conclusion: In conclusion BNP is currently a good predictor of different cardiac diseases. Journal of Current and Advance Medical Research, July 2021;8(2):125-129